2019
DOI: 10.1186/s12874-019-0686-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on use of electronic health records for research recruitment

Abstract: Background: EHR phenotyping offers the ability to rapidly assemble a precisely defined cohort of patients prescreened for eligibility to participate in health-related research. Even so, stakeholders in the process must still contend with the practical and ethical challenges associated with research recruitment. Patient perspectives on these matters are particularly important given that the success of research recruitment depends on patients' willingness to participate. Methods: We conducted 15 focus groups (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…In our previously-reported research [15], we explored patient perspectives on initial recruitment contact and similar qualitative themes emerged (see Introduction)-but patients seemed to weigh the tradeoffs differently compared to the professional stakeholder groups in the present study. Most participants in both studies found both approaches to initial contact acceptable; however, 100% of professionals said contact through physicians was acceptable compared to 75% of patients, and 66% of professionals said direct contact was acceptable compared to 95% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previously-reported research [15], we explored patient perspectives on initial recruitment contact and similar qualitative themes emerged (see Introduction)-but patients seemed to weigh the tradeoffs differently compared to the professional stakeholder groups in the present study. Most participants in both studies found both approaches to initial contact acceptable; however, 100% of professionals said contact through physicians was acceptable compared to 75% of patients, and 66% of professionals said direct contact was acceptable compared to 95% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve potential differences in perspectives reported here among professional stakeholder groups (physicians less often favored initial direct contact between researchers and patients, researchers less often favored opt in approaches, and IRBs less often favored opt out approaches) and between professionals and patients, we concur with McHugh and colleagues [9] that, "In light of how healthcare delivery has evolved toward providing more collaborative, patient-centered, and data-driven care, individual IRBs and institutions must reconsider existing policies so that recruitment can similarly evolve" (p.384). Steps toward a patient-centered approach-one that addresses stakeholder concerns about privacy and research quality while also promoting fair access to research and decisional autonomy-could include [15]: A strength of our interview design was asking participants about acceptable as well as most appropriate actions, after considering advantages and disadvantages of competing strategies from multiple viewpoints. However, interpretation of our findings is subject to some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of focus groups about research recruitment using electronic health records data, Beskow and colleagues report, trust and transparency were critical to the respondents' reactions to recruitment queries. The respondents thought that direct contact by either a researcher or their own physician was acceptable, although most thought that direct contact by the researcher would give them more control over their decision 24 …”
Section: Potential Optionsmentioning
confidence: 99%
“…These implementations are dependent on the patient's consent to partake in the trials and there are studies that investigate the process and ethics of such consent [52]. Beskow et al identified patient informed consent as a bottleneck in using EHR for randomized clinical trials.…”
Section: Emr Use In Clinical Trialsmentioning
confidence: 99%